Perbandingan tingkat kepuasan pasien Jaminan Kesehatan Nasional (JKN) di Puskesmas Andalas dan Klinik Simpang Anduring kota Padang - Muthia Larasati; Rima Semiarty; Febrian Febrian (Andalas Dental Journal, 2021)
JKN is a program implemented through Indonesian government policy to ensure the health. One of the targets in the development of JKN is patient satisfaction. In JKN system, there are high rise of health service. The primary health service starts from FKTP. Puskesmas Andalas and Simpang Anduring Clinic is a FKTP who collaborated with BPJS Kesehatan. In a structure service of JKN, consist of three services. There is primary service, secondary service and tertiary service. Oral health service included primary service. The purpose of this research to know the description of satisfaction JKN patient of service dental care in Puskesmas Andalas and Simpang Anduring Clinic, Padang. The size of the sample is 210 respondents using a consecutive sampling technique. The Result of this research showed reliability, responsiveness, assurance, empathy and tangibles in Puskesmas Andalas and Simpang Anduring Clinic still not good seen form 5 dimensions of quality service. The conclusion is seen from 5 dimensions of quality service, Puskesmas Andalas and Simpang Anduring Clinic still not got enough in providing services. Viewed by comparison betweetn Puskesmas Andalas and Simpang Anduring Clinic, satisfied of JKN patients in Puskesmas Andalas is higher than Simpang Anduring Clinic.